Linearity measurement of FTIR infrared spectral emissivity measurement facility determined using flux superposition at NIM. Issue 1 (January 2021) - Song, X; Dong, W; Yuan, Z; Lu, X; Li, Z; Qu, Y; An, B; Huan, K
Abstract: A Fournier-Transform infrared (FTIR) spectrometer using a deuterated triglycine sulfate (DTGS) detector is the radiation detective unit of the infrared spectral emissivity measurement facility of standard reference of P. R. China at NIM. The linearity of the FTIR spectral responsivity in the NIM infrared spectral emissivity measurement facility has a significant contribution to emissivity measurement. The linearity of the FTIR using the DTGS detector is experimentally measured using a flux superposition principle. A linearity measurement system of FTIR spectral responsivity is established using a high- and mid-temperature standard reference cavity blackbody radiation sources, covered the temperature range (373-1373) K. The linearity characteristics are measured in the temperature range of (473∼1273) K of the blackbody radiation sources. The measurement results with the uncertainties at the representative wavelengths of 3.9 μm and 10.6 μm are reported. The associated discussions about the linearity measurement results, including the difference at the two wavelengths, the effects caused by reflection and verifications are carried out. All the measurements in this paper are traceable to NIM.